PERLINDUNGAN HUKUM KEPADA PEMENANG LELANG ATAS OBJEK EKSEKUSI HAK TANGGUNGAN - Shilvia Rahayu Safitri; Jasman Nazar (JOURNAL OF LAW AND NATION, 2024)
This study was conducted to analyze the legal protection for the winners in the auction process of executing mortgage rights, as regulated by Law Number 4 of 1996 concerning Mortgage Rights. In this investigation, a normative research method was employed, focusing on the examination of legislation through specific case studies. Findings from this study indicate that legal protection for auction winners is divided into two categories: preventive and repressive. Preventive protection aims to ensure legal security during the acquisition period, while repressive protection is implemented after the purchase through actual execution or forcible removal of the auctioned object. This protection is regulated in the Minister of Finance Regulations and HIR Provisions. The implication of this research is the importance of upholding the rights of the auction winner based on applicable regulations to ensure fairness in the mortgage rights execution process.